2010
DOI: 10.4103/0253-7184.68993
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent HIV/AIDS: Issues and challenges

Abstract: Adolescence (10-19 years) is a phase of physical growth and development accompanied by sexual maturation, often leading to intimate relationships. Adolescent HIV/AIDS is a separate epidemic and needs to be handled and managed separately from adult HIV. The adolescents can be subdivided into student, slum and street youth; street adolescents being most vulnerable to HIV/AIDS. Among various risk factors and situations for adolescents contracting HIV virus are adolescent sex workers, child trafficking, child labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 16 publications
1
24
1
2
Order By: Relevance
“…Almost all focused exclusively on perinatally infected children and youth. Thus, our picture of disclosure to children would be enhanced by looking at rural, out-of-treatment, orphaned, boarding school, and non-perinatally infected children as well (22, 31, 51). Some research programs in progress have made steps in that direction (25, 27, 34, 45, 52); some have conducted research at community sites overcoming biases toward studying only treated populations and overcoming barriers to participation in research such as travel to health center research sites [e.g., Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all focused exclusively on perinatally infected children and youth. Thus, our picture of disclosure to children would be enhanced by looking at rural, out-of-treatment, orphaned, boarding school, and non-perinatally infected children as well (22, 31, 51). Some research programs in progress have made steps in that direction (25, 27, 34, 45, 52); some have conducted research at community sites overcoming biases toward studying only treated populations and overcoming barriers to participation in research such as travel to health center research sites [e.g., Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The articles, providing background for this review, that do describe context – sometimes in case studies, policy papers or research on allied topics such as adherence – are compelling. A few examples will suffice: dilemmas faced by a grandmother who had promised her deceased daughter to never reveal the daughter had died of AIDS, but now discovers the grandchild she is raising is HIV+ (57); disclosure occasioned in a rural district by the child having to travel alone to get care (34); the differing issues for child-headed households in post-genocide Rwanda (8); marginalized and at-risk child and youth populations in India such as street children and children pressed into sex trade (51); secrecy and collusion about illness and medicine-taking within families in a community with high stigmatization of HIV (5); cultural conflict when fathers are family decision-makers, but mothers manage health care and are being told to disclose (15); and the surprise an HIV+ child felt when told her HIV+ status by an apparently healthy HIV+ adult nurse because of the child’s assumptions about how HIV progresses (58). Again some research programs are beginning to assess not only caregiver and health-provider attitudes but attitudes and policies of surrounding communities and institutions such as health-care clinics, hospitals, churches, and schools (1, 7, 8, 52, 54, 59), leading to additional targets for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents are categorised among the vulnerable in connection to HIV prevalence (Naswa & Marfatia 2010;cf. Chisale & Buffel 2014 As much as migration brings with it positive, life-changing patterns, such as job opportunities, better health and better education, it also exposes children to abuse, exploitation and HIV and AIDS (Chisale 2014).…”
Section: Conscientising Urms About Gender Issues and Hivmentioning
confidence: 99%
“…Studies with both male and female participants have shown that alterations in body appearances have significant effects on the psychosocial well-being and quality of life of PLHIV [6,7]. Growth retardation in all forms has a negative psychological impact on adolescents for whom body image is an integral part of the adolescence phase [8]. There is limited research on ART-related lipodystrophy (a disorder of fatty tissue characterized by a selective loss of body fat) in lowand middle-income countries especially among adolescents [9], yet the prevalence of lipodystrophy is substantial in these setting [10].…”
Section: Introductionmentioning
confidence: 99%